2009
DOI: 10.1186/1746-4358-4-2
|View full text |Cite
|
Sign up to set email alerts
|

Impact of ritual pollution on lactation and breastfeeding practices in rural West Bengal, India

Abstract: Background: Breastfeeding in India is universal and prolonged. Several cultural practices are associated with lactation and breastfeeding in India, mainly revolving around the concept of ritual purity and 'hot and cold' foods, food avoidance, restricted diet after childbirth, and remaining in seclusion for a certain time period because of the polluting effects of childbirth. This study on breastfeeding practices explored how the concept of ritual pollution influenced practices after delivery, including during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
103
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(121 citation statements)
references
References 24 publications
5
103
3
Order By: Relevance
“…most common reason for delay in early initiation of breastfeeding observed was delay in shifting of mother from labour room or operation theatre, shifting of babies to NICU and various family restrictions. 12 Exclusive breastfeeding for 6 months was observed in 27% mothers, which was substantially lower than previous studies and as per NFHS 4 data of Punjab state, where it is observed to be 53% (54.8% in urban and 51.1% in rural areas of Punjab) but higher than recent studies which reported 7.8% in study done by Tiwari et al and 16.5% by Bandhyopadhay et al [13][14] Further studies indicate prevalence of exclusive breastfeeding for 6 months is generally low in low resource and developing nations. 15 However, breastfeeding promotion interventions in developing countries have shown to result in 6-fold increase in exclusive breastfeeding for 6 months to achieve MDG 4.…”
Section: Discussioncontrasting
confidence: 52%
“…most common reason for delay in early initiation of breastfeeding observed was delay in shifting of mother from labour room or operation theatre, shifting of babies to NICU and various family restrictions. 12 Exclusive breastfeeding for 6 months was observed in 27% mothers, which was substantially lower than previous studies and as per NFHS 4 data of Punjab state, where it is observed to be 53% (54.8% in urban and 51.1% in rural areas of Punjab) but higher than recent studies which reported 7.8% in study done by Tiwari et al and 16.5% by Bandhyopadhay et al [13][14] Further studies indicate prevalence of exclusive breastfeeding for 6 months is generally low in low resource and developing nations. 15 However, breastfeeding promotion interventions in developing countries have shown to result in 6-fold increase in exclusive breastfeeding for 6 months to achieve MDG 4.…”
Section: Discussioncontrasting
confidence: 52%
“…52.8 percent said that they were aware that Exclusive Breast Feeding is important for the infant, while the rest, i.e., 41.1 percent said that they were not aware about it. 76.1 percent of the respondents said that they considered that pre-lacteal feeds were very important considering its cultural component as well as the nutrient content for the baby whereas 23.9 percent said that pre-lacteal feeds were not important for the baby [41][42][43][44][45][46].…”
Section: Resultsmentioning
confidence: 99%
“…There are previous reports on the intake of special dietary food supplements during lactation; these foods are believed to improve health and lactation performance [15,40]. However, to the best of our knowledge, no study so far has reported the effect of dietary food supplements consumption on bone health of mothers.…”
Section: Discussionmentioning
confidence: 95%